Myth and the Monster Cinema - Stymeist, David H. (Anthropologica, 2022)
The project of critical anthropology may be furthered by the incorporation of the popular film into the anthropological study of myth. A structuralist analysis of King Kong (1933) reveals it to be exemplary of a body of contemporary myth. Made and explicitly set during the Depression, the Depression itself in the form of the monster is ultimately slain by the organized forces of industrial technology. Monster movies collectively represent various threats to the survival of industrial civilization, and in the vanquishing of the monster, the supremacy of the technological and ideological infrastructure of modern of life is reaffirmed and valorized.